510 Co-design of an evidence and theory-based hospital deprescribing behaviour change intervention. (13th April 2023) - Scott, S; Atkins, B; Kellar, I; Taylor, J; Keevil, V; Martin-Kerry, J; Alldred, D P; Murphy, K; Patel, M; Witham, M; Wright, D; Bhattacharya, D
Abstract: Introduction: 50% of older adults are prescribed a medicine that is unnecessary or harmful that should be deprescribed (1). CompreHensive geriAtRician-led MEdication Review (CHARMER) is a behaviour change intervention to equip geriatricians and pharmacists to proactively deprescribe. Five determinants of deprescribing have been prioritised and the following six Behaviour Change Techniques (BCTs) selected that now require designing (2): 1&2. Pros and cons and salience of consequences to address misconceptions that deprescribing is risky, 3. Restructuring pharmacists working to facilitate contribution to deprescribing 4. Social comparison to address misconceptions that patients/carers are resistant to deprescribing 5. Action planning to prioritise deprescribing and 6. Incentivising deprescribing. Aim: We aimed to co-design the content, mode of delivery and intensity of BCTs to develop a hospital deprescribing behaviour change intervention. Methods: We maximum variation sampled three hospitals to represent contextual factors likely to influence CHARMER implementation: diversity of patient population, geography, IT infrastructure maturity and include a combination of larger teaching and smaller district general hospitals. We recruited geriatricians, pharmacists and staff likely to be involved in implementation to join one co-design panel per hospital. We convened two rounds of workshops with each hospital to design BCT prototypes following the five iterative steps of design thinking: empathise, define, ideate, prototype and test. We introduced geriatrician and pharmacist personas in round 1 and panels discussed how barriers and enabler influence practice through a journey mapping exercise, followed by brainstorming ideas for how BCT(s) to address them could be operationalised. Round 2 aimed to reach consensus about which of the Round 1 BCT operationalisation ideas were most promising, and then refine their content, mode of delivery and duration/intensity. Behavioural scientist and practitioner members of the research team prepared prototypes for feedback at a final workshop attended by the three hospital panels. Results: The six BCTs were operationalised into an intervention comprising: (1 & 2) 2-hour workshop with pros and cons activities and videos of salient patient cases (3) Weekly short face-to-face pharmacist:geriatrician deprescribing discussions (4) 5-minute videos of geriatricians navigating challenging deprescribing consultations (5) Hospital deprescribing action plan template (6)Dashboard updated weekly to benchmark deprescribing activity with other hospitals Automated prompts to flag high-risk patients for deprescribing and a primary and secondary care deprescribing forum were proposed as additional BCTs. These were later excluded as they address 'memory, attention and decision processes' and a 'primary care social influence' respectively which does not align with the determinants of deprescribing (1). Conclusion: This study illustrates the integration of theory and co-design methodology for a hospital deprescribing behaviour change intervention. The development of an intervention that remains faithful to the underpinning mechanisms of action of behaviour change is a strength of this approach. Maximum variation sampling for hospital permitted representation of the 'extremes' of contextual factors but may result in an intervention that is not optimised for the majority. The intervention is undergoing feasibility testing across four English hospitals and will proceed to a definitive trial across 42 hospitals in Spring 2023 to determine effectiveness and cost effectiveness. References: 1. Gallagher P, Lang PO, Cherubini A, Topinková E, Cruz-Jentoft A, Montero Errasquín B, et al. Prevalence of potentially inappropriate prescribing in an acutely ill population of older patients admitted to six European hospitals. European journal of clinical pharmacology. 2011;67(11):1175–88. 2. Scott S, May H, Patel M, Wright DJ, Bhattacharya D. A practitioner behaviour change intervention for deprescribing in the hospital setting. Age and ageing. 2021;50(2):581–6.